2003
DOI: 10.1124/dmd.31.11.1283
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR THE VALIDITY OF CORTISOL 6β-Hydroxylation CLEARANCE AS a NEW INDEX FOR IN VIVO CYTOCHROME P450 3A PHENOTYPING IN HUMANS

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:This study uses stable isotope methodology to evaluate the validity of 6␤-hydroxylation clearance of endogenous cortisol as a new index for in vivo CYP3A phenotyping in humans. Important factors contradictory to the use of a conventional index of urinary ratio of 6␤-hydroxycortisol to cortisol (6␤-OHF/F) to evaluate in vivo CYP3A activity are also discussed. Stable isotopically labeled cortisol (3-5 mg) was orally administered to three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 20 publications
3
62
0
Order By: Relevance
“…Therefore, phenotyping of CYP3A seems to be of special importance. Some CYP3A substrates, such as midazolam, erythromycin, alprazolam, and nifedipine have been reported to be useful markers for CYP3A phenotyping; other markers are the urinary 6b-hydroxycortisol: cortisol ratio and formation clearance of 6b-hydroxycortisol and 4b-hydroxycholesterol (Karayalçin et al, 1991;Kovacs et al, 1998;Streetman et al, 2000;Bodin et al, 2001;Furuta et al, 2003;Galteau and Shamsa, 2003). It is important to select a marker that is appropriate for the characteristics of the study subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, phenotyping of CYP3A seems to be of special importance. Some CYP3A substrates, such as midazolam, erythromycin, alprazolam, and nifedipine have been reported to be useful markers for CYP3A phenotyping; other markers are the urinary 6b-hydroxycortisol: cortisol ratio and formation clearance of 6b-hydroxycortisol and 4b-hydroxycholesterol (Karayalçin et al, 1991;Kovacs et al, 1998;Streetman et al, 2000;Bodin et al, 2001;Furuta et al, 2003;Galteau and Shamsa, 2003). It is important to select a marker that is appropriate for the characteristics of the study subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, phenotyping of cytochrome CYP3A seems to be of special importance. Some CYP3A substrates such as midazolam, erythromycin, alprazolam and nifedipine, urinary 6β-hydroxycortisol to cortisol ratio; formation clearance of 6β-hydroxycortisol and 4β-hydroxycholesterol have been reported to be useful markers for CYP3A phenotyping [14][15][16][17][18][19]. Especially, 4β-hydroxycholesterol may be useful in patients with renal failure because the kinetics of 4β-hydroxycholesterol seem to be unaffected by renal function due to the slow elimination by 7α-hydroxylation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the macrolide antibiotic clarithromycin was administered to another healthy male volunteer, the inhibitory effects of clarithromycin on in vivo CYP3A activity were clearly indicated by the 6β-hydroxylation clearance of endogenous cortisol, but not by the urinary 6β-OHF/F. It has also been suggested that urinary 6β-OHF/F does not always reflect the in vivo CYP3A activity [11] . However, significant shortcomings were associated with this study by Furuta et al; these included the limited number of samples, and the lack of a comparison with probes such as MDZ and erythromycin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Furuta et al [11] found that cortisol 6β-hydroxylation clearance (Cl m(6β) ) could be a reliable index for in vivo CYP3A activity evaluation. In this study, a strong correlation between endogenous and exogenous 6β-hydroxylation clearance was shown in three healthy male volunteers.…”
Section: Introductionmentioning
confidence: 99%